(untitled) (Interdisciplinary Studies Journal, 2026)
This article is based on basic research, funded by the Araucária Foundation for Support of Scientific and Technological Development of the State of Paraná, and is being developed within the scope of the Interdisciplinary Postgraduate Program in Society and Development (PPGSeD) at Unespar/Campo Mourão. The research aims to identify the social markers of class, gender, race, disability, and old age present in the dissertations produced since the first graduating class of the program in 2016. Through bibliographic research, it presents reflections related to these markers, highlighting their intersections and implications in the constitution of social, economic, cultural, political, territorial, and other inequalities. Based on a critical, interdisciplinary, and intersectional approach, it discusses how these markers contribute to the hierarchization of individuals and groups, shaping their daily experiences, which can be of privilege or vulnerability. The social and institutional mechanisms that perpetuate inequalities are also considered.